STRATEGI HUMAN RELATIONS LEMBAGA AMIL ZAKAT (LAZ) AL AZHAR DALAM MENINGKATKAN CITRA LEMBAGA - Sri Lestari; Usman Usman; Syamsuar Syam (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2020)
An agency or company, requires an effort to create a harmonious relationship between an agency and its public. Public relations is a mediator who is between the leadership of an organization or institution with the public, both in an effort to foster internal and external community relations. Public relations activities to communicate the situation in the company to the public. This paper reviews the Public Relations Strategy of Al Azhar's Amil Zakat Institute (LAZ) in Improving the Image of Institutions through human relations, community relations, and media relations activities. This study uses qualitative methods with descriptive data analysis techniques with operational study methods. Data collection is obtained through observation, interviews, and documentation. In theory there are three public relations strategies, namely human relations, community relations, and media relations. In writing only discussed in the first part, namely the strategy of human relations of Al Azhar’s LAZ in improving the image of the institution. Activities carried out in human relations, include two things, namely: internal activities by maintaining work relations among employees and volunteer networks, and external activities by conducting social humanitarian activities.